Parliament, Parties, Polls and Islam: Issues in the Current Debate on Religion and Politics in Pakistan (American Journal of Islam and Society, 1985)
The ideological and political history of Pakistan is marked by acontinuing debate on the nature of the Islamic political system and itsconcrete manifestation in the constitutional framework of the state.Even the Objectives Resolution which was adopted in 1949 and washailed by the religious political groups as a “landmark” in the history ofIslamic constitutional thought could not bring about a broad consensusamong the politically relevant sectors of society. The three subsequentconstitutions adopted in 1956,1962, and 1973 have also failed to resolvethe controversies over the nature, characteristics, functions, andstructure of an Islamic state.The problem assumed new significance after the present martial lawregime of General Mohammad Zia-ul-Haq initiated the process ofIslamization, postponed the scheduled general elections and extended itstenure for an indefinite period. These moves were preceded by PresidentZia-ul-Haq-s expressing his aversion for the Western democratic systemand its institutions (i.e., parliament, parties, elections, etc.). He felt thatthere was no scope for such divisive institutions in an Islamic polity andthat he would introduce an alternative political system based on trulyIslamic principles. He gave no details of what he actually meant by a“true Islamic polity”, but it was apparent from his statements andactions that this “true Islamic polity” was anything but what is generallyrecognized as democratic. This polity, moreover, was not necessarilyfounded on the principle of majority rule. It was quite possible-andindeed legitimabin this system for an individual or a group tocontinue ruling the country against the wishes of the majority of thepeople. President Zia asserted that according to Islam only “rightdecisions” were to be respected and, if the majority were“misguided”, itsverdict would have to be ignored. Addressing a public meeting inIslamabad in 1983, for example, President Zia said: ...